Phytochemical Assay and in – Vitro Cytotoxicity Assessment of Cassava Peel (Manihot esculenta) from Ethanol and Ethyl Acetate Extract Against Cervical Cancer Cells (HeLa) - Soejono, Alice Hari; Dwira, Surya; Sari, Puji (UI Scholars Hub, 2024)
Introduction: Cervical cancer is a type of cancer that develops in a woman’s cervix. It is a result of HPV (Human Papilloma Virus) and is one of the deadliest types of cancer. Some cervical cancer management including chemotherapy, which until recently continues to develop to cure the condition, is relatively expensive and comes with multiple different side effects. Method: Manihot esculenta undergoes multilevel maceration with the solvent of ethanol and ethyl acetate. This leads to the formation of ethanol extract and ethyl acetate extract of Manihot esculenta that is analyzed through phytochemical assay and thin layer chromatography (TLC) to determine the phytochemical components present. This is then followed by cytotoxicity assessment against Hela cervical cancer cells using MTT test. Result: Manihot esculenta peel contains secondary metabolites including tannin, flavonoid, alkaloid, and triterpenoid. Cytotoxicity activity evaluation for ethanol shows moderate cytotoxicity with IC50 value of 228.26 μg/mL. While ethyl acetate shows active cytotoxicity activity with IC50 value of 56.47 μg/mL. The data distribution of IC50 value of all extracts is normal (p>0.05). There was a statistically insignificant difference in IC50 value between extracts based on one-way ANOVA. Conclusion: Manihot esculenta peel contains phytochemical components that are cytotoxic towards HeLa cervical cancer cells.